ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA SEPEDA MOTOR HONDA SCOOPY DI KOTA PURUK CAHU - Nurhayati Nurhayati; Agus Febrianto; Rasyidi Rasyidi (Universitas Lambung Mangkurat, 2020)
The research was motivated by the growth of motorcycle users who become a great opportunity for automotive business players, especially in the field of motorcycle. The growing potential attracted many well-known brands to enliven the motorcycle market in Indonesia. Specially, this research discuss about selling Honda Scoopy in Puruk Cahu.The purpose of this study to determine the effect of price and product quality on purchase decisions through customer satisfaction. This research type is the explanatory, data collection techniques through the quetionnaires. The sampling technique used accidential sampling technique, with a sample of 95 people. This research used quantitative method with software Smart PLS as the analysis technique. The result indicate that the price (X1) and product quality (X2) significantly can have direct influence to the purchasing decision (Y) as well as indirect influence by passing customer satisfaction (Z) as intervening variable then influence the purchasing decision.Keywords : price, product quality, purchase decision, customer satisfaction